Sequential dual-energy subtraction technique with a dynamic flat-panel detector (FPD): primary study for image-guided radiation therapy (IGRT) - Tanaka, Rie; Sanada, Shigeru; Matsui, Takeshi; Hayashi, Norio; Matsui, Osamu (Radiological physics and technology, 2008)
A sequential dual-energy subtraction technique for image-guided radiation therapy (IGRT) was developed. Here, we report on a computerized method for creating sequential soft-tissue images and the accuracy of tracking targets on the images obtained, in comparison to conventional fluoroscopic images. Two sets of sequential chest images during respiration of a normal subject were obtained with X-rays of different energy separately with a flat-panel detector (FPD). Sequential soft-tissue images were created from the two sets of sequential images consisting of real-time images and reference template images, respectively. The creation of sequential soft-tissue images consisted of three steps: one-to-one image correspondence of the two sequential images, image registration, and image subtraction in each frame. Motion tracking of lung vessels was then performed by the template-matching technique. For evaluation of the accuracy of motion tracking on the sequential soft-tissue images, the results were compared with those on the original sequential images. Sequential soft-tissue images provided more accurate tracking than the original images ( P < 0.01). There was no significant error throughout all frames in the soft-tissue images, whereas the rib shadow introduced a tracking error in the original images. The maximum errors were 4.1 ± 0.3 mm in the sequential soft-tissue images and 28.1 ± 20.0 mm in the original images. In conclusion, sequential soft-tissue images were helpful for tracking of a target affected by respiratory motion. Dual-energy subtraction has the potential to improve the accuracy of IGRT without implanted markers.